2015
DOI: 10.1007/s10971-015-3687-3
|View full text |Cite
|
Sign up to set email alerts
|

Doped microporous hybrid silica membranes for gas separation

Abstract: Hybrid silica (i.e., bis-triethoxysilylethane: BTESE) membranes doped with B, Ta or Nb were made through a sol-gel process. Triethyl borate, tantalum (V) ethoxide (TPE) and niobium (V) ethoxide (NPE) were selected as doping precursors. The doping concentration was optimized to produce sols, suitable for membrane fabrication. Thermal stability, structural analysis, crosssectional micrographs and single gas permeation experiments were performed on these membranes, and results are compared with an undoped BTESE m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…12. This suggests that densification effects due to thermal degradation of the ethylene bridge may have led to small enough pores for the Nb center to have an appreciable effect on CO 2 transport in the study of Qi, while the same sites did not influence CO 2 permselectivity in an intact BTESE-based matrix as in the study of Qureshi et al [89] Recently, a malonamide-functional membrane with an ability to disperse transition metal ions homogeneously throughout the matrix was reported [17]. Both Ce 4? and Ni 2?…”
Section: Gas Separationmentioning
confidence: 85%
See 2 more Smart Citations
“…12. This suggests that densification effects due to thermal degradation of the ethylene bridge may have led to small enough pores for the Nb center to have an appreciable effect on CO 2 transport in the study of Qi, while the same sites did not influence CO 2 permselectivity in an intact BTESE-based matrix as in the study of Qureshi et al [89] Recently, a malonamide-functional membrane with an ability to disperse transition metal ions homogeneously throughout the matrix was reported [17]. Both Ce 4? and Ni 2?…”
Section: Gas Separationmentioning
confidence: 85%
“…Qi et al explained these effects by the formation of acidic Nb sites in the matrix structure [20,87], but also by possible densification effects due to the very high thermal annealing temperature for BTESE (400-550°C in N 2 ) [86], temperatures at which thermal degradation of the organic bridges may have occurred [61,86]. Other dopants that have been introduced into BTESE and BTESM matrices by co-condensation are aluminum (Al) [88], boron (B) and tantalum (Ta) [89]. In the latter study, a much lower thermal annealing temperature of 300°C (in N 2 ) was employed.…”
Section: Gas Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…This was explained by the formation of acidic Nb sites in the matrix structure leading to strong gas adsorption. The same approach was also pursued for BTESE-derived silica (Qi et al 2010(Qi et al , 2012Qureshi et al 2015), but in these cases, the phenomenon was either observed or not, depending on the pretreatment of the BTESE membrane. Low CO 2 permeances were observed when the system was annealed at high temperatures (400-550 C in N 2 ) (Qi et al 2012) but not when lower annealing temperatures (300 C in N 2 ) were employed .…”
Section: Gas Separationmentioning
confidence: 99%
“…This lower permeance is an indication for network densification. Qureshi et al [41] investigated Nb doping to BTESE as well, though they were not successful in reproducing the low CO 2 permeance and high H 2 /CO 2 Qureshi et al [41] investigated, besides niobia doping, also boron and tantalum doping. The tantalum doped BTESE membrane showed a similar permeance and selectivity as the niobium doped membrane as described above.…”
Section: Metal Dopingmentioning
confidence: 99%